2015
DOI: 10.1080/09537287.2014.1002025
|View full text |Cite
|
Sign up to set email alerts
|

Guest editorial: information technology-enabled supply chain management

Abstract: It is widely accepted that advances in information technology (IT) will generate new opportunities when suppliers, business partners and customers work together to co-create and co-produce value. However, results from prior studies show that the mere possession of IT is unlikely to generate business value. Rather, IT creates value when information -frequently produced by IT infrastructure -is used to support complementary organizational and human resources. Still, the hypothesis that greater investment in IT w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 43 publications
(33 citation statements)
references
References 39 publications
0
30
0
3
Order By: Relevance
“…For example, Wixom et al (2013) identified 'drivers of pervasive use' and 'drivers of speed to insight' as new constructs for possible theoretical vextension in BDA adoption and value. In the similar spirit, Fosso Wamba et al (2015a) highlighted transactional, strategic and transformative business values of BDA as fertile grounds for knowledge creation. Also, Sharma et al (2014) put forward new research questions exploring the roles of resource allocation and resource orchestration processes in organizations in order to gain a deeper understanding of how BDA influences business value.…”
Section: Predictive Analyticsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Wixom et al (2013) identified 'drivers of pervasive use' and 'drivers of speed to insight' as new constructs for possible theoretical vextension in BDA adoption and value. In the similar spirit, Fosso Wamba et al (2015a) highlighted transactional, strategic and transformative business values of BDA as fertile grounds for knowledge creation. Also, Sharma et al (2014) put forward new research questions exploring the roles of resource allocation and resource orchestration processes in organizations in order to gain a deeper understanding of how BDA influences business value.…”
Section: Predictive Analyticsmentioning
confidence: 99%
“…This paper focuses on e-commerce firms that capture business value through using big data analytics (BDA). The extant literature shows that BDA could allow an e-commerce firm to achieve a range of benefits, such as: enhanced pricing strategies for products and services (Christian 2013); targeted advertising; better communication between research and development (R&D) and product development; improved customer service; improved multi-channel integration and coordination; enhanced global sourcing from multiple business units and locations, and, overall, suggesting models and ways to capture greater business value Fosso Wamba et al 2015a;Sharma et al 2014). The research question that has driven this study focuses on: how is "big data analytics" different from traditional analytics in the e-commerce environment in creating business value?…”
Section: Introductionmentioning
confidence: 99%
“…Contemporary concerns within OSCM literature, such as sustainability (Carter and Rogers, 2008;Seuring and Müller, 2008;Siegel, 2009), involve, inter alia, navigating through voluminous and unstructured data environments to facilitate business process monitoring, supply chain visibility, and improved manufacturing, automation, and efficiency (Davenport et al, 2012;Fosso Wamba et al, 2015b). Therefore, there is a growing need to understand the managerial processes, practical aspects and challenges, and business effects when utilising BD&A tools and techniques in organizations and supply chains.…”
Section: Introductionmentioning
confidence: 99%
“…Fosso Wamba et al (2015a) conducted a systematic review of big data literature to synthesise the key themes and how they may impact OSCM and the business community. In another study Fosso Wamba et al (2016) surveyed 297 Chinese IT managers and business analysts with big data and business analytic experience to examine the impact of big data on their businesses.…”
Section: Introductionmentioning
confidence: 99%